2017
DOI: 10.1038/onc.2017.227
|View full text |Cite
|
Sign up to set email alerts
|

Disrupting G6PD-mediated Redox homeostasis enhances chemosensitivity in colorectal cancer

Abstract: Glucose-6-phosphate dehydrogenase (G6PD) is a key enzyme that generates NADPH to maintain reduced glutathione (GSH), which scavenges reactive oxygen species (ROS) to protect cancer cell from oxidative damage. In this study, we mainly investigate the potential roles of G6PD in colorectal cancer (CRC) development and chemoresistance. We discover that G6PD is overexpressed in CRC cells and patient specimens. High expression of G6PD predicts poor prognosis and correlated with poor outcome of oxaliplatin-based firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
116
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(122 citation statements)
references
References 38 publications
4
116
0
2
Order By: Relevance
“…In discrepant cases, a pathologist reviewed the cases and reached the consensus. Expression level was determined according to our previous report (23). The terminal deoxynucleotidyl transferasemediated nick end labeling (TUNEL) assays were performed with the In Situ Cell Death Detection Kit (Roche, cat.…”
Section: Ihc and Tunel Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In discrepant cases, a pathologist reviewed the cases and reached the consensus. Expression level was determined according to our previous report (23). The terminal deoxynucleotidyl transferasemediated nick end labeling (TUNEL) assays were performed with the In Situ Cell Death Detection Kit (Roche, cat.…”
Section: Ihc and Tunel Analysismentioning
confidence: 99%
“…All female BALB/c nude mice (4-5 weeks old) used in our study were purchased from the Beijing Vital River Laboratory Animal Technology Co., Ltd. and housed in specific pathogen-free units. Subcutaneous mice model was performed as reported previously (22,23).…”
Section: In Vivo Tumorigenesis and Metastasis Assaysmentioning
confidence: 99%
“…Indeed, some of the main oncogenes and tumour suppressors such as p53 and K-Ras, can directly regulate the enzymes involved in this pathway [6,11,12]. Several studies showed that the inhibition of G6PD may result in the development of therapeutic strategies against tumour growth and metastasis [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies showed that GSCs can be specifically targeted by a short cell-penetrating peptide based on Cx43 (TAT-Cx43266-283) that reduces tumour growth in preclinical models 6 via c-Src inhibition 7 . The effects of TAT-Cx43266-283 on GSC metabolism found in this study highlight the therapeutic potential of this compound against glioblastoma because TAT-Cx43266-283 targets crucial proteins for glioma malignancy, namely GLUT-3, HK-2, G6PD and HIF-1ɑ [11][12][13][40][41][42] . Our in vitro, ex vivo and in vivo data show that glucose uptake is specifically impaired in GSCs through short-and long-term mechanisms involving the regulation of the activity and expression of key glucose enzymes.…”
Section: Discussionmentioning
confidence: 59%
“…Emerging data suggest that, beyond cell-intrinsic factors, nutrient availability in the tumour microenvironment can also influence drug response, hampering the efficacy of common antitumoral drugs 10 . To investigate whether this was also the case for TAT-Cx43266-283, GSCs in complete medium were treated with 50 μM At the molecular level, GSCs adapted to glucose-only medium by upregulating glucose metabolism enzymes critical for cancer cells, such as HK-2 11,12 and glucose-6-phosphate-dehydrogenase (G6PD) 40,41 , the key and ratelimiting enzyme in the pentose phosphate pathway ( Supplementary Fig. 3b).…”
Section: Tat-cx43266-283 Impairs the Metabolic Plasticity Of Gscsmentioning
confidence: 99%